How to Attract More Tourists to Korea? Possible Collaborations with China - Wenjun Zhong; Jinhwan Oh (European Regional Science Association (ERSA), 2015)
Based on the gravity model, this paper analyzes China and South Koreas tourism patterns. Using a panel data set of Chinas international tourism flows from 32 countries for 1995-2012, and Koreas international tourism flows from 152 countries for 2005-2013, this study finds that the two countries data sets are generally consistent with the predictions of the gravity model. We further investigated the predicted values of tourist flows with actual values to determine under-represented countries. Policy implications follow regarding how to attract more tourists to Korea.
Keywords: 330; gravity model; China; Korea; tourism